Multi‐catalytic Enantioselective Synthesis of 1, 3‐Diols Containing a Tetrasubstituted Fluorinated Stereocenter. Issue 17 (9th February 2022) - Shao, Na; Monnier, Valérie; Charles, Laurence; Rodriguez, Jean; Bressy, Cyril; Quintard, Adrien
Abstract: The enantioselective construction of fluorohydrins featuring a tetrasubstituted stereocenter embedded in complex frameworks represents an important challenge. Herein, we report a multicatalytic strategy enabling the stereoselective preparation of a new type of scaffold containing such a challenging fluorohydrin motif. The sequence is based on an organocatalyzed fluorination of α‐disubstituted aldehydes followed by a diastereoselective copper‐catalyzed decarboxylative aldol reaction. Reduction of the generated β‐hydroxy ketone followed by a Lewis base‐catalyzed kinetic resolution enables the isolation of original fluorinated 1, 3‐diols with perfect diastereo‐ and enantio‐control. Abstract : Through a multi‐catalytic sequence, valuable enantioenriched 1, 3‐diols containing a challenging tetrasubstituted fluorinated stereocenter could easily be prepared. The sequence involves an organocatalyzed fluorination of disubstituted aldehydes followed by a diastereoselective copper‐catalyzed aldol reaction. From the aldol adduct, ketone reduction followed by enantioselective organocatalyzed Kinetic Resolution provided the diols in >90 %  ee .